Presumptive Cytomegalovirus Retinitis as a Complication of Dyskeratosis Congenita: A Case Report - Yuxi Du; Yalong Dang (Case Reports in Ophthalmology, 2024)
Introduction: Dyskeratosis congenita is a rare genetic disorder characterized by abnormalities of the skin, nails, and oral mucosa. Retinal involvement in this condition is uncommon. Here, we present a case of a young male patient diagnosed with presumptive cytomegalovirus retinitis, ultimately found to be concomitant with dyskeratosis congenita. Case Presentation: A non-HIV-infected young male with recurrent infections, including aspergillus pneumonia and pneumocystis pneumonia, presented with presumptive cytomegalovirus retinitis in both eyes. Systemic manifestations included cutaneous hyperpigmentation, nail dystrophy, and oral mucosal leukoplakia. Genetic testing revealed a mutation in the DKC1 gene. The final diagnosis was dyskeratosis congenita complicated by presumptive cytomegalovirus retinitis. Conclusion: Cytomegalovirus retinitis can serve as an ocular complication of dyskeratosis congenita. When a patient presents with cytomegalovirus retinitis, a comprehensive systematic examination should be conducted as it indicates severe immunodeficiency.